“The Role of Traditional Games in Enhancing Artistic Skills in Children” - Xidoyeva Mahliyo Bozor qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of traditional national games in enhancing artistic skills among children. It discusses how these games can improve creativity, compositional thinking, spatial awareness, and aesthetic perception. The article also highlights practical methods for integrating traditional games into fine arts lessons to make learning more engaging and culturally relevant.